Application of web 2.0 in private university libraries of northern Nigeria using the theory of mannes library 2.0. - Shehu, Abdullahi, Bala (My University, 2020)
This paper investigated application of web 2.0 to private university libraries of northern part of Nigeria based on Mannes theory which emphasizes on changing scenario of librarianship with the presence of the web, (10) private university libraries website which are of quality and ICT compliant by Nigerian standard were surveyed to identify the presence of web 2.0 tool application and purpose for application. Only (4) 40% had applied web 2.0 tool, the most applied web tool was WebOPAC followed by social networking sites, and (1) private university library had applied RSS, no other web tool have been applied. Even with the web 2.0 boom and advantages web 2.0 provides to library professional for interaction, the application is still very much low in Nigerian libraries. The study recommends Training of library professionals, provision of ICT infrastructure, restructuring of library school curriculum.
Supplemental Materials: https://osf.io/m2wrk/
Keywords: Application; Private University libraries; Web2.0; websites